Prolonged Expression of Procoagulant Activity of Human Platelets Degranulated by Thrombin - Kinlough-Rathbone, Raelene L; Perry, Dennis W (Thrombosis and Haemostasis, 1995)
Platelets are exposed to thrombin when they take part in arterial thrombus formation, and they may return to the circulation when they are freed by fibrinolysis and dislodged by flowing blood. Thrombin causes the expression of procoagulant activity on platelets, and if this activity persists, the recirculating platelets may contribute to subsequent thrombosis. We have developed techniques to degranulate human platelets by treatment with thrombin, and recover them as single, discrete platelets that aggregate in response to both weak and strong agonists. In the present study we examined the duration of procoagulant activity on the surface of thrombin-degranulated platelets by two methods: a prothrombinase assay, and the binding of 125I-labeled annexin. Control platelets generated 0.9 ± 0.4 U thrombin per 107 platelets in 15 min. Suspensions of thrombin-degranulated platelets formed 5.4 ± 0.1 U thrombin per 107 platelets in this time. Binding of 125I-annexin V was also greater with thrombin-treated platelets than with control platelets (controls: 1.7 ±0.1 ng annexin/107 platelets; thrombin-degranulated platelets: 6.8 ± 0.2 ng annexin/107 platelets). With thrombin-degranulated platelets, increased procoagulant activity and annexin binding persisted for at least 4 h after degranulation and resuspension, indicating that the catalytic activity for the prothrombinase complex is not reversed during this time. These platelets maintained their ability to aggregate for 4 h, even in response to the weak agonist, ADP. Thus, platelets that have taken part in thrombus formation and returned to the circulation may contribute to the promotion of further thrombotic events because of the persistence of procoagulant activity on their surface.